USED OF FISHING TOOLS AND FISHING AID IN KENDARI OCEAN FISHERY PORT - Suratna, Suratna; Khikmawati, Liya Tri; Jaya, Made Mahendra; Rahman, Alfian Fatur (Jurnal Segara, 2024)
Fishing Gear is equipment used by fishermen to catch fish and other marine animals. The operation of the fishing gear itself is not always alone, some fishermen use fishing aids to increase the effectiveness and efficiency of fishing activities. Some types of Fishing aids commonly used by fishermen are lamps and fish aggregating devices (FADs) used to collect fish and power blocks/axles, or line haulers used by fishermen to facilitate the operation of the fishing gear. This study aims to find out what fishing gear and fishing aids are in Kendari and analyze their compliance with existing regulations. The research activities were carried out for 2 months, namely from November to December 2023 at the Kendari Fisheries Port. The type of data collected is qualitative data including construction data from each API in Kendari through direct observation. The data collected is then analyzed descriptively. Based on the data obtained, the types of Fishing Gear used by vessels based at the Kendari PPS are 5 (five) fishing gears, consisting of Tuna Hand Line, Huhate, Purse Seine, Hand Line, Squid Fishing. This fishing gear is an active fishing gear. Fishing aids used by fishermen at PPS Kendari include LED lights, Pakurung and fish aggregating devices. There are still violations related to the use and operation of fishing gear (purse seines), as well as the installation of fish aggregating devices. To avoid violations of the use of fishing gear and fishing aids, currently there is still a need for supervisory officers and equipment support using technology.